2020
DOI: 10.1128/aac.00261-20
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efflux Pump Expression in Candida Mutants Results in Decreased Manogepix Susceptibility

Abstract: Manogepix is a broad-spectrum antifungal agent that inhibits glycosylphosphatidylinositol (GPI) anchor biosynthesis. Using whole-genome sequencing, we characterized two efflux-mediated mechanisms in the fungal pathogens Candida albicans and Candida parapsilosis that resulted in decreased manogepix susceptibility. In C. albicans, a gain-of-function mutation in the transcription factor gene ZCF29 activated expression of ATP-binding cassette transporter genes CDR11 and SNQ2. In C. parapsilosis, a mitochondrial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…▪ Regarding 4. Some fungi have an efflux pump similar to that found in bacteria [37,38]. To overload this pump, high dosing is needed.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…▪ Regarding 4. Some fungi have an efflux pump similar to that found in bacteria [37,38]. To overload this pump, high dosing is needed.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…In [36] sind die MG dargestellt und weitere Therapiehinweise aufgeführt. ▪ Ad 4: Ähnlich wie Bakterien können auch manche Pilze eine "efflux pump" haben [37,38]. Um diese zu überlasten, gilt die Devise "nicht kleckern, sondern klotzen".…”
Section: Diskussion Und Ausblickunclassified
“…Two C. parapsilosis and C. albicans mutants were identified that demonstrated 4- to 8-fold decreased susceptibility to MGX in which the gwt1 gene sequence was similar to the wild-type [ 42 ]. These mutants were further investigated and the change in MIC was determined to be efflux-mediated [ 49 ]. The C. parapsilosis mutant contained a mitochondrial deletion, which activated expression of the major facilitator superfamily transporter gene MDR1 .…”
Section: Resistancementioning
confidence: 99%
“…The C. albicans mutant demonstrated a gain-of-function mutation in the transcription factor gene ZCF29 , which activated expression of the ATP-binding cassette transporter genes CDR11 and SNQ2 . These two mutants also showed 2- and 4-fold decreased susceptibility to FLC, but not AMB or CAS [ 42 , 49 ]. These data are consistent with the observation that a subset of FLC resistant mutations in several species may lead to small increases in MGX MIC values [ 50 ].…”
Section: Resistancementioning
confidence: 99%
See 1 more Smart Citation